(3dhGbM GdCfhGQ GdbOSjI aj efGbH GdYdeGA hGdUhajIs - (3YHO GdhgGH Hf CMeO Hf Ydj GdMfaj GdTYQGfj,J (B973 (3g` s ((3GdeOQSI GdbGOQjI (B- (3GdbGgQI s)
(3ChdgG (B:s
(3agPg WHbGJ YXjeI PcQJ ajgG LedI UGdMI ef efGbH GdUGdMjf hGdYdeGA GdYGedjf s
(3BNQgG (B:s
(3aEf ef de jYJbO ai YdeGA YUQg aGJg eOOge hGdMeO ddg QH GdYGdejf s
(3GdfSNI HNW GdeDdas
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B180 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B339s
Keywords: (3GdJGQjNs